MANAJEMEN PEMBELAJARAN BERDIFERENSIASI PADA KELAS GEMUK DI SEKOLAH DASAR: STUDI KASUS IMPLEMENTASI STRATEGI DI SEKOLAH DASAR PERKOTAAN - Guntur Dwi Purwanto (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The phenomenon of "overcrowded classes" in urban elementary schools with a student ratio of 35 to 40 students creates significant obstacles to the realization of meaningful, personalized learning. Heterogeneous student characteristics and limited space are the main focus of problems that demand agile instructional management innovation at Cimanggu 02 Public Elementary School. This qualitative case study research was conducted through systematic stages that included participant observation, in-depth interviews, and a comprehensive analysis of curriculum documents. The research findings indicate that efficient time allocation was successfully managed through the use of non-verbal communication codes as attention anchors and the implementation of autonomous visual schedules for students. Flexible grouping strategies were implemented by engineering limited space into various functional learning stations, including the use of corridors as controlled group activity zones. In the media dimension, the principle of ecological sensitivity was applied through the conversion of recycled materials and the optimization of open-source digital platforms to overcome the limitations of the school's minimal operational budget. Field data confirmed that overcrowding that exceeds the ideal threshold triggers a real psychological burden for educators in the field. The main conclusion of the study confirms that managerial resilience and adaptive creativity of teachers can transform infrastructure barriers into inclusive learning environments. Nevertheless, standardizing a more humane teacher-student ratio is an absolute prerequisite for central authorities in ensuring national quality equity. ABSTRAK Fenomena "kelas gemuk" di sekolah dasar perkotaan dengan rasio tiga puluh lima hingga empat puluh siswa menciptakan hambatan signifikan bagi terwujudnya pembelajaran personal yang bermakna. Heterogenitas karakteristik siswa dan keterbatasan lahan menjadi fokus masalah utama yang menuntut inovasi manajemen instruksional lincah di SD Negeri Cimanggu 02. Penelitian kualitatif studi kasus ini dilakukan melalui tahapan sistematis yang meliputi observasi partisipatif, wawancara mendalam, serta bedah dokumen kurikulum secara menyeluruh. Temuan penelitian menunjukkan bahwa efisiensi alokasi waktu berhasil dikelola melalui penggunaan kode komunikasi non-verbal sebagai jangkar perhatian dan penerapan jadwal visual otonom bagi peserta didik. Strategi pengelompokan fleksibel dijalankan dengan merekayasa keterbatasan ruang menjadi berbagai stasiun belajar fungsional, termasuk pemanfaatan selasar sebagai zona aktivitas kelompok yang terkendali. Dalam dimensi media, prinsip kepekaan ekologis diterapkan melalui konversi material daur ulang dan optimalisasi platform digital sumber terbuka guna mengatasi keterbatasan anggaran operasional sekolah yang minim. Data lapangan menegaskan bahwa kepadatan yang melebihi ambang batas ideal ini memicu beban psikologis nyata bagi pendidik di lapangan. Simpulan utama penelitian menegaskan bahwa resiliensi manajerial dan kreativitas adaptif guru mampu mentransformasi hambatan infrastruktur menjadi lingkungan belajar yang inklusif. Meskipun demikian, standarisasi rasio guru dan siswa yang lebih manusiawi menjadi prasyarat mutlak bagi otoritas pusat dalam menjamin keadilan kualitas nasional.